Genetic relationships between anther and stigma traits revealed by QTL analysis in two rice advanced-generation backcross populations - Saran Khumto (2018)
© 2017, Springer Science+Business Media B.V., part of Springer Nature. Anther and stigma size are critical floral traits that influence outcrossing in rice (Oryza sativa), a crop that is predominantly self-fertilizing. The efficiency of hybrid rice seed production depends on efficient outcrossing ability of parental lines, which is promoted by increased anther and stigma size. Phenotypic correlations between anther and stigma traits have been observed in many studies; however, evidence for this relationship is unclear and the genetic basis remains to be elucidated. To examine this relationship and to identify quantitative trait loci (QTLs) for increased anther and stigma size, we developed two advanced backcross QTL mapping populations derived from a cross between a Thai elite indica crop variety (SPR1) and an accession of common wild rice (O. rufipogon Griff.), which is predominantly outcrossing. One mapping population was selected for increased anther size while the other was selected for increased stigma size. We mapped QTLs for anther size and stigma size in both populations. Bulked segregant analysis was used to identify molecular markers associated with the selected traits. A total of 16 significant QTLs associated with anther and stigma traits were identified across the two populations, and these were located in five genomic regions on four chromosomes. Whereas three of these regions have been previously reported, two of them are newly identified and should be further explored for improving outcrossing ability in rice. The co-localization of QTL for anther and stigma traits strongly suggests some degree of shared developmental basis for these traits.